Chemical Composition and Bioactivity Characteristics of Pimpinella Anisum Essential Oil against Trichophyton rubrum - Ali Jalil Obaid (Journal of Global Pharma Technology, 2017)
Background: The present study was conducted to assess the phytochemical and bioactive characteristics of anise oil on metabolic activity of Trichophyton rubrum. Methods: Essential oil was extracted from anise seeds using a Clevenger-type apparatus. Phyto chemical analysis of active material was carried out, through TLC accompanied autoradiography, high performance liquid chromatography (HPLC) and GC-MS analyses were proceeded to relate the chemical profile with their antifungal activity. Minimum inhibitory concentrations were determined using the micro wells dilution method. Inhibitory effect of crude anise oil and anethole was investigated against T. rubrum. Cytotoxic effects of anise oil and anethole was concluding using MTT assay. Effects and interaction of anethole with ergosterol of fungi cell membrane was assayed. Results: Qualitative TLC, HPLC analysis revealed the present of anethole in the essential oil from anise seeds. One volatile compound in the extracts of anise oil sample was identified as anethole under the chromatographic conditions. GC-MS analysis revealed that anethole is the major compound in essential oil of P. anisum, in which trans-anethole was 96.8%, then Himachalene (1.84%), other components were also present but less than 1% e.g. Estragole, cyclohexene and 2-Methoxy-5-(1-propenyl) phenol. The tested strains of this fungus revealed substantial sensitivity pattern to assayed anethole. Results showed that there was total growth inhibition of the dermatophytes isolates at minimal inhibitory concentrations (MIC) between 15.6 μ g/m L for crude oil and 7.5 μ g/m L for anethole. MTT assay revealed that anethole is safe as phototherapeutic agents, when it is having no effects on normal cell, but shown anticancer activity against cancer cell. Conclusions: The obtained results suggested that essential anise oil and anethole might be a potential source of new antimicrobial agents and could be valuable as an alternative drug against T. rubrum.Keywords: Trichophyton rubrum, Anise essential oil, TLC-bio autography, HPLC, GC-MS, Antifungal activity.